Proliferating tumor cells mimick glucose metabolism of mature human erythrocytes. Issue 12 (18th June 2019) - Ghashghaeinia, Mehrdad; Köberle, Martin; Mrowietz, Ulrich; Bernhardt, Ingolf
ABSTRACT: Mature human erythrocytes are dependent on anerobic glycolysis, i.e. catabolism (oxidation) of one glucose molecule to produce two ATP and two lactate molecules. Proliferating tumor cells mimick mature human erythrocytes to glycolytically generate two ATP molecules. They deliberately avoid or switch off their respiration, i.e. tricarboxylic acid (TCA) cycle and oxidative phosphorylation (OXPHOS) machinery and consequently dispense with the production of additional 36 ATP molecules from one glucose molecule. This phenomenon is named aerobic glycolysis or Warburg effect. The present review deals with the fate of a glucose molecule after entering a mature human erythrocyte or a proliferating tumor cell and describes why it is useful for a proliferating tumor cell to imitate a mature erythrocyte. Blood consisting of plasma and cellular components (99% of the cells are erythrocytes) may be regarded as a mobile organ, constantly exercising a direct interaction with other organs. Therefore, the use of drugs, which influences the biological activity of erythrocytes, has an immediate effect on the entire organism. Abbreviations : TCA: tricarboxylic acid cycle; OXPHOS: oxidative phosphorylation; GSH: reduced state of glutathione; NFκB: Nuclear factor of kappa B; PKB (Akt): protein kinase B; NOS: nitric oxide synthase; IgG: immune globulin G; H2 S: hydrogen sulfide; slanDCs: Human 6-sulfo LacNAc-expressing dendritic cells; IL-8: interleukin-8; LPS: lipopolysaccharide; ROS: reactive oxygen species; PPP: pentose phosphate pathway; NADPH: nicotinamide adenine dinucleotide phosphate hydrogen; R5P: ribose-5-phophate; NAD: nicotinamide adenine dinucleotide; FAD: flavin adenine dinucleotide; O2 ●− : superoxide anion; G6P: glucose 6-phosphate; HbO2 : Oxyhemoglobin; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GAP: glyceraldehyde-3-phosphate; 1, 3-BPG: 1, 3-bis-phosphoglycerate; 2, 3-BPG: 2, 3-bisphosphoglycerte; PGAM1: phosphoglycerate mutase 1; 3-PG: 3-phosphoglycerate; 2-PG: 2-phosphoglycerate; MIPP1: Multiple inositol polyphosphate phosphatase; mTORC1: mammalian target of rapamycin complex 1; Ru5P: ribulose 5-phosphate; ox-PPP: oxidative branch of pentose phosphate pathway; PGK: phosphoglycerate kinase; IFN-γ: interferon-γ; LDH: lactate dehydrogenase; STAT3: signal transducer and activator of transcription 3; Rheb: Ras homolog enriched in Brain; H2 O2 : hydrogen peroxide; ROOH: lipid peroxide; SOD: superoxide dismutase; MRC: mitochondrial respiratory chain; MbFe 2+ -O2 : methmyoglobin; RNR: ribonucleotide reductase; PRPP: phosphoribosylpyrophosphate; PPi : pyrophosphate; GSSG: oxidized state of glutathione; non-ox-PPP: non-oxidative branch of pentose phosphate pathway; RPI: ribose-5-phosphate isomerase; RPE: ribulose 5-phosphate 3-epimerase; X5P: xylulose 5-phosphate; TK: transketolase; TA: transaldolase; F6P: fructose-6-phosphate; AR2: aldose reductase 2; SD: sorbitol dehydrogenase; HK: hexokinase; MG: mehtylglyoxal; DHAP: dihydroxyacetone phosphate; TILs: tumor-infiltrating lymphocytes; MCTs: monocarboxylate transporters; pHi: intracellular pH; Hif-1α: hypoxia-induced factor 1; NHE1: sodium/H + (Na + /H + ) antiporter 1; V-ATPase: vacuolar-type proton ATPase; CAIX: carbonic anhydrase; CO2 : carbon dioxide; HCO3 − : bicarbonate; NBC: sodium/bicarbonate (Na + /HCO3 − ) symporter; pHe: extracellular pH; GLUT-1: glucose transporter 1; PGK-1: phosphoglycerate kinase 1 Graphical Abstract: